Editorial: Environmental data, governance and the sustainable city - Evans, James; Pregnolato, Maria; Rogers, Christopher D. F.; Harris, Jim A.; Topping, David (Frontiers, 2024)
The availability of new types of environmental data has the potential to change the ways in which cities are governed to improve their sustainability, resilience, and livability. Distributed sensors delivering real-time data can improve the monitoring and management of urban systems, as well as enabling robust assessments of policy and planning interventions. Real-time high-resolution sensor data provides a wealth of new opportunities for understanding systems and the interaction of physical, technical and anthropogenic activity. These benefits include long (multi-year) data baselines of high-resolution data enabling new statistical and artificial intelligence approaches; real-time analytics and visualizations supporting decision support systems; vulnerability or incipient failure detection to enable (proactive) maintenance rather than (subsequent, reactive) repair; parameterization of urban digital twins of physical and natural systems for simulation and prediction and what-if scenario testing; post-event analysis and post-intervention analysis across multiple phenomena at different timescales; and digital playback of systems when singularities, oversights, mistakes or other unforeseen events occur.
Keywords: data; cities; sustainability; urban governance and management; sensors; Internet of Things (IoT); smart city-urban management-policies for sustainability; monitoring